PENGARUH SUHU AKTIVASI TERHADAP KUALITAS KARBON AKTIF BIJI DURIAN - Sahdinal Adi; Masthura Masthura; Abdul Halim Daulay (JISTech (Journal of Islamic Science and Technology), 2022)
This research was conducted to utilize durian seed waste into activated carbon and aims to identify the characteristics of the durian seed activated carbon produced from the activation temperature alteration. With an experimental method with a quantitative approach, the process of making durian seed activated carbon was tested by carbonization using an oven at a temperature of 200 oC for 180 minutes, then temperature activation with alterations of 500, 600, and 700 oC was held for 120 minutes in the furnace, and after it was added with chemical activation by using a 1,5 M H2SO4 solution for 24 hours of immersion. The analysis seen is to test the water content, volatile matter content, ash content, bound carbon content, and to see the surface morphology of activated carbon using SEM (Scanning Electron Microscopy). The results of the test obtained values for water content (6,83 – 12,73%), volatile matter content (16,98 – 26,89%), ash content (7,85 – 12,04%), bound carbon content(61,66 – 75,17%), with an increase in the activation temperature there is a tendency to decrease the value of water content, volatile matter content, ash content, and there is an increase in the value of bound carbon content. And visible cavities on the surface of the activated carbon along with the increase in activation temperature.